Effects of methotrexate, Moringa oleifera, and Andrographis paniculata extracts on the myocardial and aortic tissue of streptozotocin-nicotinamide-induced hyperglycemic rats - Pamungkas, Dimas Bathoro Bagus; Kalanjati, Viskasari Pintoko; Abdurachman; Aditya, Dwi Martha Nur; Nasution, Muhammad Husni Fansury; Syamhadi, Maya Rahmayanti (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Methotrexate (MTX) could lower glucose levels in type 1 diabetes mellitus, while Moringa oleifera and Andrographis paniculata supplementations have similar effects on hyperglycemia. This study aimed to analyze the effects of MTX, M. oleifera, and A. paniculata leaf extracts on the myocardial interleukin (IL)-6 and the histopathology of the left ventricle and aorta. METHODS 49 rats were divided equally into 7 groups: negative control and diabetic induced by streptozotocin-nicotinamide (STZ-NA) injection consisting of positive control (STZ-NA only), M. oleifera (500 mg/kgBW/day), A. paniculata (500 mg/kgBW/day), MTX (7 mg/kgBW/week), MTX (7 mg/kgBW/week)+M. oleifera (500 mg/kgBW/day), and MTX (7 mg/kgBW/week)+A. paniculata (500 mg/kgBW/day). We analyzed oral MTX, M. oleifera, and A. paniculata leaf extracts’ effects on random blood glucose, myocardial IL-6, and cardiac histopathology of STZ-NA-induced hyperglycemic male rats. Data were analyzed using Wilcoxon and Kruskal–Wallis tests. RESULTS Myocardial IL-6 in the M. oleifera group was significantly lower compared to the positive control group (p = 0.041). Compared to the positive control group, the myocardial necrosis and aortic intima–media thickness in the MTX+A. paniculata group were significantly reduced (p = 0.005 and 0.001, respectively). CONCLUSIONS MTX, M. oleifera, and A. paniculata showed antihyperglycemic effect, both individually and in combination. A. paniculata leaf extract had a significant cardioprotective effect in STZ-NA-induced hyperglycemia.